A translocation-competent pore is required for Shigella flexneri to escape from the double membrane vacuole during intercellular spread - Raab, Julie E; Harju, Tucker B; Toperzer, Jody D; Duncan-Lowey, Jeffrey K; Goldberg, Marcia B; Russo, Brian C (bioRxiv, 2024)
Type 3 secretion systems (T3SSs) enable bacterial virulence by translocating virulence proteins (effectors) into host cells. require T3SS to invade and to spread between cells in the colon. In order to spread, forms membrane protrusions that push into the adjacent host cell. These protrusions are resolved into double membrane vacuoles (DMVs) that the bacteria quickly escape. The mechanisms required for escape from the DMV are poorly understood, but the T3SS translocon pore protein IpaC is essential. Here, we show IpaC forms a pore that is competent for translocation of T3SS effectors as bacteria spread between cells. To do so, we used a genetic approach to test mutations of IpaC that disrupt its ability to translocate and to form pores. We show that during spread, IpaC is efficiently inserted into the plasma membrane, the membrane-embedded IpaC forms pore complexes, and the IpaC-dependent pores translocate effectors that are necessary for to escape the DMV. We further show that T3SS activation is regulated through a distinct mechanism at spread compared to at invasion; activation of T3SS secretion does not require pore formation during spread. Thus, we show that a distinct regulation of the T3SS during intercellular spread enables the placement of effectors both around and across membranes of the DMV. Altogether, this study provides new insights into how escapes the DMV. The type 3 secretion system (T3SS) is required for virulence in many bacterial pathogens that infect humans. The T3SS forms a pore through which virulence proteins are delivered into host cells to enable bacterial infection. Our work investigates the translocon pore protein IpaC, which is essential not only for bacteria to invade cells, but also for bacteria to spread between cells. An ability to spread between cells is essential for pathogenesis, thus understanding the mechanisms that enable spread is important for understanding how infection causes illness. We show that IpaC delivers virulence factors across the host membrane for to efficiently spread. This study furthers our understanding of the mechanisms involved in T3SS secretion and of translocon pore function during intercellular spread.